Social media for health promotion: A visual analysis of "TB Proof" South Africa's Facebook page - Asongu Acha-Anyi; Paul N. Acha-Anyi; Simplice Asongu; Vanessa Tchamyou (African Governance and Development Institute (AGDI), 2020)
Health promotion is an educational tool that can be used to educate and create awareness of health issues through various media forms. The purpose of this study was to explore the use of social media (TB Proof South Africa's Facebook page) in creating tuberculosis (TB) awareness. A qualitative case study approach was used to collect data from TB Proof South Africa's Facebook page. An in-depth visual analysis of TB Proof South Africa's Facebook page was carried out over a five-month period (from 1 February to 30 June 2017). The analysis of TB Proof South Africa's Facebook page was conducted in order to determine the use of social media for health promotion. Such a comprehensive analysis was aimed at determining if the visuals on this page create awareness on TB as an illness. Common themes were identified including, TB medication, TB patients and healthcare workers raising awareness on TB. The findings have potential implications for health promotion efforts using social media.
Keywords: 330; Health promotion; social media; facebook; tuberculosis (TB); health communication; TB Proof South Africa